A Cost Effective sensorless vector control of 4- Switch 3-Phase Inverter Fed IM using MRAS - Haitham Zaki Azazi; M. K. Metwally; Z. M. El-Barbary (International Journal of Power Electronics and Drive Systems (IJPEDS), 2011)
This paper investigates performance of a Model reference adaptive system (MRAS) based cost-effective drive system of an induction motor (IM) for low-cost applications. In this paper, the MRAS is used as a speed estimator and the motor is fed from a four-switch three-phase (FSTP) inverter instead of a conventional six-switch three-phase (SSTP) inverter. This configuration reduces the cost of the inverter, the switching losses, and the complexity of the control algorithms. The robustness of the proposed MRAS-based FSTP inverter fed IM drive is verified by Experimental results at different operating conditions. A comparison of the proposed FSTP inverter fed IM drive with a conventional SSTP inverter system is also made in terms of the performance analysis. The proposed FSTP inverter fed IM drive is found quite acceptable considering its performance, cost reduction and other advantages.DOI: http://dx.doi.org/10.11591/ijpeds.v1i2.100